2012
DOI: 10.1177/1934578x1200700303
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Preparation of Incensole and Incensole Acetate, and Quantification of These Bioactive Diterpenes in Boswellia papyrifera by a RP-DAD-HPLC Method

Abstract: Incensole and incensole acetate, found in incense, are encouraging potent bioactive diterpenic cembrenoids, inhibiting Nuclear Factor-κB activation. Furthermore, incensole acetate elicits psycho-activity in mice by activating the TRPV3 channels in the brain. Starting from crude extracts of the incense species Boswellia papyrifera Hochst., a convenient procedure for the efficient large-scale synthesis of incensole and its acetate is presented. Additionally, a reversed-phase, diode-array-detection, high-performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Both compounds are potent bioactive diterpenic cembrenoids that activate TRPV3. In addition to TRPV3 activation in the skin with unknown functional effects, IA causes anxiolytic‐like and antidepressive‐like behavioural effects in mice that are absent in Trpv3 knockout animals, also indicating a still unknown role of TRPV3 in the CNS (Moussaieff et al ; Moussaieff & Mechoulam, ; Paul & Jauch, ). TRPV3 is also expressed in a subpopulation of brainstem serotonergic neurons.…”
Section: Trpv3 Identitymentioning
confidence: 99%
“…Both compounds are potent bioactive diterpenic cembrenoids that activate TRPV3. In addition to TRPV3 activation in the skin with unknown functional effects, IA causes anxiolytic‐like and antidepressive‐like behavioural effects in mice that are absent in Trpv3 knockout animals, also indicating a still unknown role of TRPV3 in the CNS (Moussaieff et al ; Moussaieff & Mechoulam, ; Paul & Jauch, ). TRPV3 is also expressed in a subpopulation of brainstem serotonergic neurons.…”
Section: Trpv3 Identitymentioning
confidence: 99%
“…However, no incensole was found in the B. serrata fractions while trace amount was detected in the fractions of B. sacra . Previous study of Paul and Jauch () showed the presence of incensole in different grades of methanolic extract of B. papyrifera in the range 18.8–24.9% using RP‐DAD‐HPLC. Our results are in complete agreement with those published (Paul and Jauch, ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous study of Paul and Jauch () showed the presence of incensole in different grades of methanolic extract of B. papyrifera in the range 18.8–24.9% using RP‐DAD‐HPLC. Our results are in complete agreement with those published (Paul and Jauch, ). Thus it can be concluded that incensole is genus‐specific.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations